Two new species of Geodiscelis Michener & Rozen (Hymenoptera: Apoidea: Colletidae) with a phylogenetic analysis and subgeneric classification of the genus - Packer, Laurence; Dumesh, Sheila (Zootaxa, 2014)
Two new species of the genus Geodiscelis are described: Geodiscelis nazcalinea Packer & Dumesh, sp. nov. from Peru (the first record of the genus from that country) and G. phisquiri Packer & Dumesh, sp. nov. from northern Chile. The new species are most closely related to G. longiceps, but differ primarily in having somewhat less elongate heads and in details of the male terminalia. A key to the five known species of the genus is provided as are the results of a phylogenetic analysis based upon 68 characters, and the genus is formally divided into three subgenera: Geodiscelis s. str. Michener and Rozen, Geodiscelis (Nazcoediscelis) Packer and Dumesh, subgenus nov. and Geodiscelis (Thaumoediscelis) Packer and Dumesh, subgenus nov. The two new species described herein belong to subgenus Geodiscelis (Nazcoediscelis). Figures of the most important characters are provided. Tiquilia sp. (Boraginaceae) is the probable floral host of both new species and it is suggested that all species are ground-nesters. Sexual dimorphism in an unusual character is recorded for G. thaumaskelos Packer.